2020
DOI: 10.7759/cureus.10446
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of Statins in the Light of Non-Alcoholic Fatty Liver Disease and Non-Alcoholic Steatohepatitis

Abstract: Statins, the lipid-lowering drugs, and non-alcoholic fatty liver disease (NAFLD)/non-alcoholic steatohepatitis (NASH), a lipid-related pathology, share a complex relationship, one known to be hepatotoxic and other being hepatic injury. NASH is an unresolved mystery in terms of treatment. Could statins prove to be a promising solution due to their pleiotropic properties in addition to the cholesterol-lowering effect? This study aims to find statin effectiveness in NAFLD/NASH treatment and prevention of associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Statins are potent cholesterol-lowering agents and evidenced-based drugs to reduce CV outcomes. Their cholesterol-lowering efficacy is expected to be beneficial for NAFLD, which is characterized by aggregation of free cholesterol into hepatocytes[ 22 , 23 ]. Besides, statins have been suggested to exert variable lipid-independent pleiotropic benefits, including antioxidant, anti-thrombotic, anti-fibrotic and anti-inflammatory actions as well as endothelial function improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Statins are potent cholesterol-lowering agents and evidenced-based drugs to reduce CV outcomes. Their cholesterol-lowering efficacy is expected to be beneficial for NAFLD, which is characterized by aggregation of free cholesterol into hepatocytes[ 22 , 23 ]. Besides, statins have been suggested to exert variable lipid-independent pleiotropic benefits, including antioxidant, anti-thrombotic, anti-fibrotic and anti-inflammatory actions as well as endothelial function improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the dysfunction of LSECs promotes activation of KCs, which in turn contributes to the morphological changes and activation of LSECs, and this interaction leads to exacerbation of liver inflammatory response in the early stage of NAFLD. Certainly, ameliorating endothelial dysfunction of LSECs can improve liver inflammation in animal models by manipulating the NO signal pathway using sildenafil or simvastatin (Tateya et al, 2011;Wang et al, 2013;Ahsan et al, 2020).…”
Section: Dysfunction Of Liver Sinusoidal Endothelial Cells Promotes Imentioning
confidence: 99%
“…Praliciguat, a soluble guanylate cyclase stimulator, effectively reduced inflammation, fibrosis, and steatosis by enhancing NO signaling in preclinical NASH models (Hall et al, 2019). Besides, improvement of the NO/cGMP signaling pathway by using phosphodiesterase-5 inhibitor sildenafil or simvastatin prevented liver inflammation in NAFLD rodents fed HFD (Tateya et al, 2011;Wang et al, 2013;Ahsan et al, 2020).…”
Section: Targeting Nitric Oxide Signaling To Improve Nonalcoholic Fatmentioning
confidence: 99%
“…Furthermore, iNOS inhibition alleviated liver endothelial dysfunction, reduced nitrooxidative stress and delayed the development of liver injury 65 . Another latest study reported that statins may restore a healthy LSEC and HSC by inhibiting the activation of HSC through modulating the expression of iNOS and eNOS 66 . But in fact, there are few studies about the changes of iNOS in aging LSECs and the subsequent effects in chronic liver diseases during aging.…”
Section: Aging‐related Lsecs and Liver Inflammationmentioning
confidence: 99%